Analisis Penerapan Kesantunan Berbahasa Dalam Podcast Deddy Corbuzzier “GUS MIFTAH MARAH !INI JELAS HINA NABI MUHAMMAD !ANW ROHINGNYA BAGAIMANA GUS!?” - Shifa Aulia Putri (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
Talking or chatting is an activity that humans do in their daily lives. In a conversation or discussion, everyone should apply polite language. Language politeness also has different applications, such as for interlocutors who are younger than us, older and on the same level as us. Apart from looking at age, language politeness is also usually related to a person's rank so that its application varies. So the aim is to analyze the politeness of language contained in Deddy Corbuzzier's podcast entitled "Gus Miftah is Angry! This clearly insults the Prophet Muhammad! ANW How about the Rohingya Gus!?”. The method used in this analysis is the literature study method. The theory used in this analysis uses pragmatic theory. Based on the results that have been obtained, the politeness of the language used in this content, in my opinion, is actually used more dominantly by Gus Miftah, starting from speaking words, conveying opinions, and making analogies with something he wants to convey. In this analysis the author found that the implication contained in it is that politeness in language is very important to use in everyday conversations, apart from minimizing misunderstandings that arise due to not paying attention to politeness in language, but politeness in language can also give the impression and assessment of other people regarding etiquette. and our politeness.